USULAN PERANCANGAN SISTEM KOMPENSASI DENGAN MENGGUNAKAN POINT RATING SYSTEM (Studi Kasus: PT Pabrik Kaos Aseli) - Sukwadi, Ronald; Gerald, Franky (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
Compensation is an important factor affecting how and why people choose to work at a organization. PT. Pabrik Kaos Aseli must be reasonably competitive and fair compensation system to attract and retain competent employees. The point rating system is the most widely used among job evaluation methods. It breaks down jobs into various compensable factors and places weights, or points, on it. Compensable factors identify a relative job value commonly present through-out a group of jobs. The factors are derived from the job analysis. Education, job complexity, responsibility, effort, and working environment are identified as compensable factors and weighted heavily. To reduce subjectivity, a group of people familiar with the jobs makes such determination. Once points have identified for all factors, the total points for a job are computed. After that, all jobs are grouped together into pay grades. The highest relative job value is Manufacturing Manager (7341.6) and the lowest one is Diesel & Workshop Operator (3622.2). To determine the pay structure, the interpolation method 1:3 is used with total cost increasing 7.55 %.